(untitled) (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
The terms antibody and immunoglobulin (Ig) are frequently used interchangeably. However, the term antibody is used more frequently in health care settings. When a B cell matures in response to antigen exposure, it becomes a plasma cell capable of producing antibodies.